Prognostic relevance of early radiologic response to induction chemotherapy in pediatric rhabdomyosarcoma: A report from the International Society of Pediatric Oncology Malignant Mesenchymal Tumor 95 study. Issue 5 (6th December 2017) - Vaarwerk, Bas; van der Lee, Johanna H.; Breunis, Willemijn B.; Orbach, Daniel; Chisholm, Julia C.; Cozic, Nathalie; Jenney, Meriel; van Rijn, Rick R.; McHugh, Kieran; Gallego, Soledad; Glosli, Heidi; Devalck, Christine; et al.
Abstract : BACKGROUND: Early response to induction chemotherapy is used in current European guidelines to evaluate the efficacy of chemotherapy and subsequently to adapt treatment in pediatric patients with rhabdomyosarcoma (RMS). However, existing literature on the prognostic value of early radiologic response on survival is contradictory; here the prognostic value is analyzed with data from the International Society of Pediatric Oncology (SIOP) Malignant Mesenchymal Tumor 95 (MMT‐95) study. METHODS: This study examined 432 Intergroup Rhabdomyosarcoma Study Grouping III (macroscopic residue) patients enrolled in the SIOP MMT‐95 study with a response assessment after 3 courses of chemotherapy (a 2‐dimensional assessment). Patients with progressive disease (PD) after 3 courses of chemotherapy were excluded (n = 7). Failure‐free survival (FFS) and overall survival (OS), calculated with the Kaplan‐Meier method, were compared for 3 groups (complete response [CR]/partial response [PR], objective response [OR], and no response [NR]). The prognostic impact of early response was assessed through the calculation of Cox proportional hazards. RESULTS: After 3 courses of chemotherapy, 85.2% of the patients had CR/PR, 8.6% had OR, and 6.3% had NR. For all patients, the 5‐year FFS and OS rates were 60% (95% confidence interval [CI], 56%‐65%) and 74% (95% CI, 70%‐78%), respectively. However, a Cox proportional hazards regression analysis revealed no significant difference in FFS or OS between the response groups. The adjusted hazard ratios for an OR and NR were 1.09 (95% CI, 0.63‐1.88) and 0.81 (95% CI, 0.39‐1.67), respectively, for FFS and 0.91 (95% CI, 0.47‐1.76) and 1.27 (95% CI, 0.61‐2.64), respectively, for OS. CONCLUSIONS: No evidence was found for the idea that early radiologic response to chemotherapy is prognostic for survival for patients with RMS. Treatment adaptation based on early response (except for patients with PD) should, therefore, no longer be incorporated into future studies. Cancer 2018;124:1016‐24. © 2017 American Cancer Society . Abstract : The prognostic relevance of an early radiologic response in rhabdomyosarcoma is assessed in pediatric patients included in the International Society of Pediatric Oncology Malignant Mesenchymal Tumor 95 study. No evidence is found for the idea that an early response to induction chemotherapy is prognostic for survival; therefore, subsequent treatment should no longer be adapted on the basis of the radiologic response.